2022
DOI: 10.1007/s00167-021-06800-8
|View full text |Cite
|
Sign up to set email alerts
|

High accuracy of a new robotically assisted technique for total knee arthroplasty: an in vivo study

Abstract: Purpose Over the last decade, robotic TKA gained popularity for improving the accuracy of implant positioning and reducing outliers in limb alignment comparing to conventional jig-based TKA. Hypothesis of this study was that this newly designed robotically assisted system will achieve a high level of accuracy for bone resection. Purpose of the study was to evaluate the accuracy of the system. Methods For this study, 75 knees in 75 patients were operated using a new, rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 27 publications
2
19
0
1
Order By: Relevance
“…178.2 ± 1.2 in all patients. [23] In our study, we found the angles to be compatible with the literature. There were some limitations in our study.…”
Section: Discussionsupporting
confidence: 91%
“…178.2 ± 1.2 in all patients. [23] In our study, we found the angles to be compatible with the literature. There were some limitations in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, while we analysed the learning curve on implant component sizing, we were unable to report on the learning curve associated with component positioning. However, other studies have reported on component positioning and limb alignment with the use of robotic systems [ 11 , 17 , 22 , 30 ]. Third, we have reported that there were no adverse events associated with the introduction of the system in this centre.…”
Section: Discussionmentioning
confidence: 99%
“…The ROSA® (Robotic Surgical Assistant) Knee system (Zimmer Biomet, Warsaw, Indiana, USA) for TKA was recently introduced. ROSA can be considered collaborative robotics, where the surgeon remains in charge of the procedure but collaborates with a smart robotic tool to perform the surgery with high accuracy and reproducibility [ 2 , 21 , 22 ]. The advantages of ROSA compared with other RA TKA include: requiring only radiographs for pre-operative planning, a collaborative robotic system where the robot completes the surgeon skills, and predictive robotics with machine learning incorporated into the system [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beim mechanischen Alignment gelten dabei Abweichungen von mehr als 3°als Outlier, beim individualisierten Alignment ist dieser Korridor wahrscheinlich sogar kleiner. Die überwiegende Literatur vergleicht die unterschiedlichen dargestellten Technologien jeweils gegen den manuellen Standard, und wenig überraschend zeigt sich für alle Systeme ein Vorteil pro Robotik in Bezug auf die jeweils untersuchten radiologischen Parameter [33,34,35,36]. Vergleichende Studien zwischen robotischen Systemen und der konventionellen Navigation in Hinblick auf die Operationspräzision (radiologisches Alignment) sind kaum verfügbar, und bisher konnte kein wesentlicher Unterschied gezeigt werden [37].…”
Section: Merkeunclassified